The potential of liquid biopsies. Issue 2 (March 2016) - Buder, Anna; Tomuta, Christian; Filipits, Martin
Abstract : Purpose of review: This article discusses the current status and applications of liquid biopsy in nonsmall cell lung cancer (NSCLC). Recent findings: The discovery of genetic alterations which are responsible for the development and progression of NSCLC led to the identification of a new generation of molecular biomarkers. However, in NSCLC, it is often difficult in clinical practice to obtain sufficient tumor material for genetic analyses. Therefore, analyses of tumor-specific genetic alterations in the serum or plasma of the patients are particularly valuable because they can provide temporal measurements of the total tumor burden as well as identify specific mutations that arise during therapy. The procedure of taking blood samples to detect tumor-specific genetic alterations is termed 'liquid biopsy'. In particular, it can be used for a variety of clinical and research applications, including response assessment in epidermal growth factor receptor ( EGFR )-mutated NSCLC patients receiving EGFR tyrosine kinase inhibitor therapy. It has been demonstrated that liquid biopsy is a fast and easy way to obtain information on tumor burden and assess the changes of the molecular nature of a tumor during the course of therapy. However, because of the limited amount of tumor material in the blood and yet insufficient knowledge of specific cancer biomarkers, extensive research has to be continued in this field to implement this method into clinical routine. Summary: In this review, we highlight the opportunities and clinical as well as research applications of liquid biopsy in NSCLC patients.